1975
DOI: 10.1007/bf01070878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endoscopic examination of colon tumors in rats

Abstract: This study is an evaluation of the use of endoscopic examination to detect MNNG-induced large-bowel tumors in rats. The smallest human fiberbronchoscope was used as a colonoscope for the rats and the full length of the distal large bowel was visualized. The correct diagnosis rate in all rats with and without large-bowel tumors was 94%. Of rats with colon tumors, 85% were correctly diagnosed endoscopically. Even tumors 1 or 2 mm in diameter were detected. The examination was easy and reliable. This procedure ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The authors successfully performed TC on 37 of 39 rats with a pediatric bronchoscope. Colonoscopy limited to the splenic flexure in rats has been previously reported [5,8]. Recently, colonoscopy in mice was reported, although the mean length of insertion was 3 cm [6].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors successfully performed TC on 37 of 39 rats with a pediatric bronchoscope. Colonoscopy limited to the splenic flexure in rats has been previously reported [5,8]. Recently, colonoscopy in mice was reported, although the mean length of insertion was 3 cm [6].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, colonoscopy in mice was reported, although the mean length of insertion was 3 cm [6]. However, these studies did not address the question as to what extent TC is reproducible [5][6][7][8]. The next challenge is to use the working channel of a fiberscope to inject a cell suspension into the cecal wall of the rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At week 11, the rats of the untreated group were submitted to endoscopic examination of the large bowel according to a method reported previously (Narisawa et al 1975;Merz et al 1981), to confirm that no grossly detectable large bowel tumors had developed up to this time. The rats were sacificed and autopsied at weeks 21 or 31.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported on attempts to perform colonoscopy in rats (1)(2)(3)(4)(5)(6)(7)(8)(9). However, in these studies, the rats were either large and old, the bowel was not optimally prepared, a total colonoscopy was not performed or no biopsies were taken.…”
Section: Introductionmentioning
confidence: 99%